Ultra Structural Studies of Macroalgae Collected from Coromandal Coast, India for Biofuel Production - Sanniyasi, Elumalai; Natesan, Senthil Kumar; Selvarajan, Ramganesh (International Journal of Bio-resource and Stress Management, 2012)
Seven species of marine macro algae belonging to Chlorophyta, Phaeophyta and Rhodophyta were surveyed, collected from Coromandal coast, India and studied for their lipid composition and its accumulation for the future biodiesel production. Variability of chemical components and production of lipid granules are specific in macro algae and there is also an evidence for temporal variability in macro algal lipid composition. The lipids of algae have wide application in production of fuel. It was observed that lipid composition of macro algae in the sequence of members belonged to Phaeophyta>Chlorophyta>Rhodophyta. In this study we successfully localized the lipid bodies of seven macro algal strain by their ultra structural studies and Nile blue stain method. However, further research work should be carried out from different marine macro algae species for biofuel production to meet out the energy crisis globally in future.